A closed testing procedure for comparing successive exponential populations with respect to location parameter. Issue 3 (1st February 2018) - Singh, Parminder; Singh, Navdeep
ABSTRACT: Consider k independent random samples such that i th sample is drawn from a two-parameter exponential population with location parameter μ i and scale parameter θ i, i = 1, …, k . For simultaneously testing differences between location parameters of successive exponential populations, closed testing procedures are proposed separately for the following cases (i) when scale parameters are unknown and equal and (ii) when scale parameters are unknown and unequal. Critical constants required for the proposed procedures are obtained numerically and the selected values of the critical constants are tabulated. Simulation study revealed that the proposed procedures has better ability to detect the significant differences and has more power in comparison to exiting procedures. The illustration of the proposed procedures is given using real data.